(untitled) (Advancements in Homeopathic Research, 2022)
The article on osteomyelitis encapsulates the advance study in catastrophic manner. The disease covering both stages of infection either its periprosthetic – joint infection and osteonecrosis condition of the bone. The innovative understanding with appropriate procedure is given in detail for progressive or uncontrolled condition of the patient. An inflammatory or serious condition of the bone and its structure in later stages caused by pyogenic infection. Myobacteria is rarely causing primary epiphyseal osteomyelitis. Medullary superficial or localized osteomyelitis developed on the various affecting site of bone. Subsequent bone damage is the end result of this ailment. The sequelae of osteomyelitis vary, depending on age at onset, site of infection, presence or absence of foreign bodies, and presence or absence of adjoining joint infection. An impaired vascularity occurs in the infected area that results in dead space/bone and repeated occurrence of bone infection may travel into the irreversible form causing the person restless, although suffering from great despodency. Altered immune defense mechanism may result in exaggerating the disease due to various abnormal conditions as in diabetic wound or from insufficient blood supply. A proper intervention simultaneously with diagnosis by corresponding symptomatology and investigation is essential to understand the pathological process along with the case progression. Homoeopathy can aid the process of recovery in cases of osteomyelitis when the best selected similimum along with miasmatic inference taken into consideration.